Challenges introduced by heterogeneous devices for Wi‐Fi–based indoor localization. (14th February 2019) - Machaj, Juraj; Brida, Peter; Majer, Norbert
Summary: In the recent time, Wi‐Fi–based indoor positioning attracts a high number of researchers worldwide because of its relatively easy implementation on widely available smart phones. Indoor positioning services can potentially open new markets for service providers and, thus, allow new ways to increase their income. A number of Wi‐Fi–enabled devices have grown significantly as well as coverage of buildings with Wi‐Fi signals, which can be considered ubiquitous nowadays. Recently, there has been a vast number of novel algorithms proposed for Wi‐Fi signals; however, they were mostly tested using only one type of device. In this paper, we will investigate the feasibility of Wi‐Fi–based positioning on different devices and highlight some of the problems that researchers have to face during the proposal of novel positioning algorithms. We have tested different devices in both laboratory and real conditions to see how they perform and which parameters can have a negative impact on the performance of the positioning system.